Comparison between the effect of marble powder and some metal oxides on the flame resistance of unsaturated polyester - نعمان رؤيا (Latakia University Journal -Engineering Sciences Series, 2024)
The research aims to study the resistance of unsaturated polyester containing 4% marble powder to combustion at high temperatures under conditions similar to combustion conditions in industrial facilities, and to compare its behavior with other samples containing the same percentage of aluminum oxide and magnesium oxide. The samples were exposed to the oxyacetylene flame within a distance (6 cm) between the tip of the cone of the moderate oxyacetylene flame and the center of the sample for a time of (1 min). The results showed similarity in the drilling time and mass loss rate for both samples containing marble powder and aluminum oxide, while samples containing magnesium oxide gave the best values. The flame resulting from burning the polyester sample containing aluminum oxide and marble powder spreads heterogeneously over the surface of the sample, and the smoke rising upon burning is dense, While the flame in the magnesium oxide sample maintained its color and nature, with a lower smoke density.